(untitled) (diségno, 2025)
This contribution, developed within the broader context of a reflection on the role of drawing in the conceptual phase of the design process, analyzes how the adoption of a specific analogical projective representation system aligns with adherence to a particular theoretical orientation in composition. As a mediator between the design concept and its gradual final configuration, drawing becomes an expression of design intent. It is an essential tool for the designer, who can explore examples and solutions drawn from historical tradition and the reference context, reinterpreting and enriching them with new potential and meaning. Drawing is not a neutral tool, but is always linked to the architectural culture that produces it, shaping design choices. This highlights the non-neutrality of representation as a form of language, linked both to the cultural attribution of meaning to the graphic sign anchored in a specific historical moment and to the ways in which the author employs it to convey a design intention. Today, technological evolution has led to the proliferation of a wide range of digital tools capable of influencing design practice itself. The research to which this contribution refers has shown how digital technologies can restore a central role to drawing in the conceptual phase of design, offering designers innovative tools to explore new creative possibilities.